2016
DOI: 10.1039/c6tc03957j
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive structure–function correlation of photoactive ionic π-conjugated supermolecular assemblies: an experimental and computational study

Abstract: Experimental and computational structure–function study of an organic crystalline photoconductor composed of oppositely charged ionic porphyrins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
77
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(83 citation statements)
references
References 91 publications
6
77
0
Order By: Relevance
“…2E). After 150-min solvent annealing, these aggregates transitioned into uniform square crystals with lateral dimensions of 200 to 500 nm and identifiable crystal faces, indicative of the emergent monoclinic crystal habit (34), as seen in Fig. 2F.…”
Section: Resultsmentioning
confidence: 93%
“…2E). After 150-min solvent annealing, these aggregates transitioned into uniform square crystals with lateral dimensions of 200 to 500 nm and identifiable crystal faces, indicative of the emergent monoclinic crystal habit (34), as seen in Fig. 2F.…”
Section: Resultsmentioning
confidence: 93%
“…For single crystal XRD evaluation, a Bruker D8 VENTURE single crystal diffractometer equipped with a Ga METALJET X-ray source (1.341398 Å) and Photon 100 detector was used for data acquisition from single crystal BP samples. The details of data collection and structural refinement for the free-base and metallated crystals are presented elsewhere [28][29][30].…”
Section: Materials and Sample Preparationmentioning
confidence: 99%
“…Each crystal was examined by XPS (x-ray photoelectron spectroscopy) to verify its stoichiometry and the actual protonation of the porphyrin tectons; spectra and analysis were published earlier [18,20,28,29,[34][35][36]. We note that heating the BP solids up to 130 °C did not modify their elemental charges or composition, based on X-ray photoelectron spectroscopy, (XPS) measurements [18,20,28,29,36]. Thermogravimetric analysis (TGA) combined with XPS showed that the crystals experienced reversible loss of water from within their crystalline channels at temperatures below 110 °C and became amorphous with annealing above 125 °C [29,30].…”
Section: Composition and Morphologymentioning
confidence: 99%
See 2 more Smart Citations